2015
DOI: 10.1039/c4ra15196h
|View full text |Cite
|
Sign up to set email alerts
|

Formation of NaP zeolite from fused fly ash for the removal of Cu(ii) by an improved hydrothermal method

Abstract: Fly ash with a Si : Al ratio of 3.63 has been converted to a zeolite of high Cu2+ sorption capacity using a fusion conversion process and an improved hydrothermal method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Among various types of zeolite, NaP is one of the most interesting structured zeolites with intersecting channels of 0.26 nm×0.49 nm. The NaP zeolite is also useful for its small pore size for the removal of toxic and radioactive waste species like As, Cs, Sr, Ba, Pb, U as well as heavy metals from waste water . The unit‐cell formulae, structure type, and CEC of some of the most important synthetic zeolites containing different Si/Al ratio described elsewhere in the literature are summarized in Table for ease of understanding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among various types of zeolite, NaP is one of the most interesting structured zeolites with intersecting channels of 0.26 nm×0.49 nm. The NaP zeolite is also useful for its small pore size for the removal of toxic and radioactive waste species like As, Cs, Sr, Ba, Pb, U as well as heavy metals from waste water . The unit‐cell formulae, structure type, and CEC of some of the most important synthetic zeolites containing different Si/Al ratio described elsewhere in the literature are summarized in Table for ease of understanding.…”
Section: Introductionmentioning
confidence: 99%
“…The NaP zeolite is also useful for its small pore size for the removal of toxic and radioactive waste species like As, Cs, Sr, Ba, Pb, U as well as heavy metals from waste water. [14][15][16] The unit-cell formulae, structure type, and CEC of some of the most important synthetic zeolites containing different Si/Al ratio described elsewhere in the literature 17,18 are summarized in Table 1 for ease of understanding. It has shown that the CEC of zeolite is directly dependent on Si:Al ratio in the zeolite.…”
mentioning
confidence: 99%
“…It is noteworthy that the recycling of effluents in the synthesis led to the complete dissolution of the silica and alumina amount present in the waste, resulting in highly pure NaP1. Although NaP1 zeolite is also usually synthesized from fly ash, the presence of unreacted quartz and mullite as a result of the lower solubility of these minerals in alkali solution is frequently observed (Deng and Ge, 2015;Querol et al, 2002;Szala et al, 2015;Wałek et al, 2008). Moreover, as observed in the XRD profiles, the plays an important role in the zeolite crystallization (Xu et al, 2010).…”
Section: Effect Of the Effluents Recycling On The Bench-scale Synthesmentioning
confidence: 99%
“…The worldwide consumption of zeolites is growing every year as a result of the increasing use of these materials in numerous industrial applications, such as water remediation (Gonzalez et al, 2015;Maretto et al, 2014), catalysis (Mazur et al, 2016), detergents, gas separation, membranes (Cundy and Cox, 2005;Yilmaz et al, 2012), etc. Zeolites can be obtained not only from chemical reagents, but also from diverse wastes, generally silica-rich precursors with very low alumina contents, such as fly ash (Deng and Ge, 2015;Querol et al, 2002), rice husk ash (Dey et al, 2012;Othman Ali et al, 2011), or kaolin-type precursors (Bessa et al, 2017) that, in general, involve pretreatments of the waste at high temperature to induce its conversion to more reactive products.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies also demonstrate economic feasibility to manufacture zeolitic adsorbents from coal fly ash thereby allowing its potential utilization [14,15]. There are several existing methods for production of zeolites from CFA, such as hydrothermal conversion using alkaline solutions [8,16,17], microwave-assisted [2], ultrasound-assisted [4,18,19], fusion followed by hydrothermal synthesis [20][21][22][23], and salt-thermal production [24] process. However, hydrothermal synthesis, that is multiphase crystallization including both amorphous and crystalline solid phases and at least one liquid phase [25], is still the most promising and widely applied method.…”
Section: Introductionmentioning
confidence: 95%